Transcatheter aortic valve implantation with the novel‐generation Navitor device: Procedural and early outcomes. Issue 1 (12th May 2022) - Corcione, Nicola; Berni, Andrea; Ferraro, Paolo; Morello, Alberto; Cimmino, Michele; Albanese, Michele; Nestola, Luisa; Bardi, Luca; Pepe, Martino; Giordano, Salvatore; Biondi‐Zoccai, Giuseppe; Rigattieri, Stefano; et al.
Abstract: Transcatheter aortic valve implantation (TAVI) has proved beneficial in patients with severe aortic stenosis, especially when second‐generation devices are used. We aimed at reporting our experience with Navitor, a third‐generation device characterized by intrannular, large cell, and cuffed design, as well as high deliverability and minimization of paravalvular leak. Between June and December 2021, a total of 39 patients underwent TAVI with Navitor, representing 20% of all TAVI cases. Mean age was 80.0 ± 6.7 years, and 14 (36.8%) women were included. Severe aortic stenosis was the most common indication to TAVI (37 [97.4%] cases), whereas 2 (5.3%) individuals were at low surgical risk. Device and procedural success was obtained in all patients, with a total hospital stay of 6.6 ± 4.5 days. One (2.9%) patient required permanent pacemaker implantation, but no other hospital events occurred. At 1‐month follow‐up, a cardiac death was adjudicated in an 87‐year‐old man who had been at high surgical risk. Echocardiographic follow‐up showed no case of moderate or severe aortic regurgitation, with mild regurgitation in 18 (47%), and none or trace regurgitation in 20 (53%). The Navitor device, thanks to its unique features, is a very promising technology suitable to further expand indications and risk‐benefit profile of TAVI.